Role of Ayurveda in the Management of Prameha w.s.r to Diabetes Mellitus-A Review - Jagtap, Umesh Balaso; Mohite, Priyadarshani Ashok; Shah, Sonal (International Research Journal of Ayurveda & Yoga, 2021)
Background In today’s world, prediabetes is more common than diabetes, and the pace at which prediabetes is converted to diabetes is also rising. Prediabetes is an intermediate stage of hyperglycemia in which the glycemic level is above normal but below the Diabetic glycemic threshold level, which affects around 471 million people worldwide. The ancient Vedas and the Ayurvedic well characterize Prameha as a global problem. An attempt is made here to examine Prameha by compiling a number of references. Aims and Objective: The purpose of this paper is to review the well-documented Ayurvedic idea of the Prameha Roga, as the prevalence of diabetes is increasing in society and is becoming increasingly difficult to avoid and control due to its complexity. Material and methods- Brihatrayee, Laghutree, and other Ayurveda literatures, articles related to Prameha are compiled. Review mainly focused on description in ancient literature. Results- This article explained Ayurvedic concept of diabetes and diabetic complications. The present review article shows the anti-diabetic effects of various mentioned herbs in ayurvedic texts. Conclusion- Prameha references can be found in the Vedas, Puranas, and other literary works. It is extensively mentioned as enumerated in Ayurvedic treatises. An effective physician should understand these fundamental ideas, and with this knowledge, they will be able to provide better care to their patients. As a part of pharmacotherapy, Ayurvedic principles for the treatment of ‘Atisthaulya’ & Kaphaja prameha should be used wisely to treat prediabetes and prevent it from progressing to diabetes.